The Role of Design Artifacts in Design Theory Construction - Jodi Forlizzi (Artifact, 2008)
Abstract As a discipline evolves, intellectual issues come into focus, and the outcomes of systematic inquiry grow in importance. The discipline of design is facing such a time, as scholars, researchers, and practitioners are devoting attention to creating categories for design practice and design research, articulating methods and processes, and, in some cases, building new design theories. The field of Human–Computer Interaction (HCI) is also experiencing an evolutionary broadening in scope that creates the need for design research. Many designers working in the HCI research community have expressed an increased interest in research through design, a research approach that employs methods and processes from design practice. However, without an agreed form of practice, evaluation, and outcome, it is hard to consistently develop design theory from research to design outcomes. In this paper, the authors begin to identify specific outcomes of research through design that form the basis for theory production. They present the research through design process and two different approaches of research through design (philosophical and grounded) that can lead to formation of design theory. They identify that extensible, systemic approaches to research through design are the most promising ones for developing design theory, and illustrate with examples.